2022
DOI: 10.3389/fneur.2022.931915
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characteristics of stroke in Zanzibar–a hospital-based prospective study in a low-income island population

Abstract: BackgroundStroke in adults is a critical clinical condition and a leading cause of death and disability globally. Epidemiological data on stroke in sub-Saharan Africa are limited. This study describes incidence rates, stroke types and antecedent factors among patients hospitalized with stroke in Zanzibar.MethodsThis was a prospective, observational study of stroke patients at hospitals in Unguja, Zanzibar. Socioeconomic and demographic data were recorded alongside relevant past medical history, medicine use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(44 reference statements)
0
2
1
Order By: Relevance
“…14 A recently published study from Zanzibar looking at hospital admissions with stroke over a 1 year period found very high rates of stroke admissions, whereby, among 720 participants overall, 463 (64.3%) participants were experiencing a first-ever stroke, and 223 (31.0%) a recurrent stroke. 15 The rate of in-hospital mortality in this study was 23.6% which was lower compared with the 27% reported in general medical inpatients admitted during the study period. The increased mortality of patients who had a stroke was associated with comorbidities such as hypertension 96 (41.9%), diabetes 26 (27.7%) and other NCDs.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…14 A recently published study from Zanzibar looking at hospital admissions with stroke over a 1 year period found very high rates of stroke admissions, whereby, among 720 participants overall, 463 (64.3%) participants were experiencing a first-ever stroke, and 223 (31.0%) a recurrent stroke. 15 The rate of in-hospital mortality in this study was 23.6% which was lower compared with the 27% reported in general medical inpatients admitted during the study period. The increased mortality of patients who had a stroke was associated with comorbidities such as hypertension 96 (41.9%), diabetes 26 (27.7%) and other NCDs.…”
Section: Discussioncontrasting
confidence: 64%
“…A recently published study from Zanzibar looking at hospital admissions with stroke over a 1 year period found very high rates of stroke admissions, whereby, among 720 participants overall, 463 (64.3%) participants were experiencing a first-ever stroke, and 223 (31.0%) a recurrent stroke. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Patients in the register were upon informed consent regularly followed-up by telephone calls and in-person visits until 1 year after stroke onset to measure a range of clinical and patient-reported outcomes. Several publications using the register data have been published to date, 2,3 and more are in development. While the register was set up to allow maintenance after the end of the study period, this has not happened.…”
mentioning
confidence: 99%